2008
DOI: 10.2337/dc07-1159
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes- and Nondiabetes-Related Lower Extremity Amputation Incidence Before and After the Introduction of Better Organized Diabetes Foot Care

Abstract: OBJECTIVE -There is a lack of continuous longitudinal population-based data on lower extremity amputation (LEA) in the U.K. We present here accurate data on trends in diabetesrelated (DR) LEAs and non-DRLEAs in the South Tees area over a continuous 5-year period.RESEARCH DESIGN AND METHODS -All cases of LEA from 1 July 1995 to 30 June 2000 within the area were identified. Estimated ascertainment using capture-recapture analysis approached 100% for LEAs in the area. Data were collected longitudinally using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
171
1
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(191 citation statements)
references
References 24 publications
8
171
1
11
Order By: Relevance
“…In early 2008, Canavan et al reported that diabetes-related lower extremity amputations in the North of England reduced over a 5-year period of time during which improvements in the organization of diabetes care were implemented [16].…”
Section: Where Are We Going?mentioning
confidence: 99%
“…In early 2008, Canavan et al reported that diabetes-related lower extremity amputations in the North of England reduced over a 5-year period of time during which improvements in the organization of diabetes care were implemented [16].…”
Section: Where Are We Going?mentioning
confidence: 99%
“…Moreover, treatment itself is very challenging and often needs to be long lasting. It requires not only expert interference, orthopaedic appliances and antimicrobial drugs but also costly topical dressings and inpatient care [22]. Not surprisingly, this leads to substantial economic burden.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors are involved in the development of foot ulcers, including peripheral neuropathy, PVD, limited joint mobility and repeated trauma from abnormal load distribution on the foot [22]. The underlying causes of foot ulcers are usually irreversible and chronically progressive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is deemed to enable a more systematic treatment of diabetic foot ulcers, a shorter period of healing, and fewer amputations resulting from foot ulcers (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%